Lucid dreaming : a concise guide to awakening in your dreams and in your life - LaBerge, Stephen (Boulder, Colo : Sounds true, 2009)
In dreams awake -- A psychobiological model of dreaming -- Learning lucid dreaming : methods for developing the skill of lucid dreaming -- The practical dreamer : applications of lucid dreaming -- Lucid dream work : from nightmares to wholeness -- Life as a dream : awake in your dreams and alive in your life. CD. Your present state of consciousness and the lucid dream state (9:42) -- Guided reality test (4:33) -- The mnemonic induction of lucid dreams (5:18) -- Dream lotus and flame technique (8:53) -- Trance induction of lucid dreaming: day (18:40) -- Trance induction of lucid dreaming: night (18:42).
boek